Viral metagenomics revealed diverse CRESS-DNA virus genomes in faeces of forest musk deer - Liu, Qi (Virol J, 2020)
BACKGROUND: Musk deer can produce musk which has high medicinal value and is closely related to human health. Viruses in forest musk deer both threaten the health of forest musk deer and human beings. METHODS: Using viral metagenomics we investigated the virome in 85 faeces samples collected from forest musk deer. RESULTS: In this article, eight novel CRESS-DNA viruses were characterized, whole genomes were 2148 nt–3852 nt in length. Phylogenetic analysis indicated that some viral genomes were part of four different groups of CRESS-DNA virus belonging in the unclassified CRESS-DNA virus, Smacoviridae, pCPa-like virus and pPAPh2-like virus. UJSL001 (MN621482), UJSL003 (MN621469) and UJSL017 (MN621476) fall into the branch of unclassified CRESS-DNA virus (CRESSV1–2), UJSL002 (MN621468), UJSL004 (MN621481) and UJSL007 (MN621470) belong to the cluster of Smacoviridae, UJSL005 (MN604398) showing close relationship with pCPa-like (pCRESS4–8) clusters and UJSL006 (MN621480) clustered into the branch of pPAPh2-like (pCRESS9) virus, respectively. CONCLUSION: The virome in faeces samples of forest musk deer from Chengdu, Sichuan province, China was revealed, which further characterized the diversity of viruses in forest musk deer intestinal tract.